1981
DOI: 10.1128/jb.145.1.50-60.1981
|View full text |Cite
|
Sign up to set email alerts
|

Cell wall turnover in batch and chemostat cultures of Bacillus subtilis

Abstract: Wall turnover was studied in Bacillus subtilis. The loss of radioactively labeled wall polymers was followed during exponential growth in batch and chemostat cultures. Turnover kinetics were identical under all growth conditions; pulse-labeled wall material was lost with first-order kinetics, but only after exponential growth for 1 generation time after its incorporation. Similarly, continuously labeled cells showed an accelerating decrease in wall-bound radioactivity starting immediately after removal of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

1981
1981
2007
2007

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 29 publications
2
25
0
Order By: Relevance
“…This would imply that, at the membrane, newly made peptidoglycan chains are heavily loaded with anionic polymers and that specific excision of many of the anionic polymers (linked to small peptidoglycan fragments) would occur in the turnover-sensitive layer of the wall (see reference 9). As was shown clearly by pulse-label experiments no peptidoglycan (and, most likely, no anionic polymers) is lost from the turnover-resistant inner wall layers (9). So all peptidoglycan-anionic polymer complexes released must originate from excision in the outer layers, at the rates indicated by k in Table 1 for peptidoglycan and the anionic polymer.…”
Section: Fragments Of Cell Wall Peptidoglycan Havementioning
confidence: 80%
See 3 more Smart Citations
“…This would imply that, at the membrane, newly made peptidoglycan chains are heavily loaded with anionic polymers and that specific excision of many of the anionic polymers (linked to small peptidoglycan fragments) would occur in the turnover-sensitive layer of the wall (see reference 9). As was shown clearly by pulse-label experiments no peptidoglycan (and, most likely, no anionic polymers) is lost from the turnover-resistant inner wall layers (9). So all peptidoglycan-anionic polymer complexes released must originate from excision in the outer layers, at the rates indicated by k in Table 1 for peptidoglycan and the anionic polymer.…”
Section: Fragments Of Cell Wall Peptidoglycan Havementioning
confidence: 80%
“…In a previous report (9), we showed that analysis of the way by which a specific radioactive peptidoglycan label was lost from B. subtilis by turnover provided some insight into the mechanisms of wall growth in this organism. Based on kinetic data, the conclusion (1,23) was reinforced that wall turnover in bacilli occurs from the outer wall layer and that wall surface enlargement takes place by spreading of peptidoglycan (9). The rate of wall turnover calculated from those previous experiments, however, referred merely to the peptidoglycan amino sugar t Present address: Gist-Brocades N. V., Microbiology Research Laboratory, Poatbus 1, 2600 MA Delft, The Netherlands.…”
Section: Fragments Of Cell Wall Peptidoglycan Havementioning
confidence: 97%
See 2 more Smart Citations
“…Kinetic analysis of the cell wall turnover was initiated in Wouters' laboratory [17], but we have recently extended their treatment [15]. The Dutch kinetic model supposed that layers progressively moved outwardly as intact lamellae.…”
Section: Side Wall Turnovermentioning
confidence: 99%